Urachal mucinous cystadenoma in infant: First case report in infant and review of literature - Barbara Bogaert; Berenice Tulelli; Marine Rodesch; Caroline Pregardien; Sandrine Rorive; Pierre Lingier (Elsevier, 2021)
Introduction: As only ten cases have been described in current literature, urachal mucinous cystadenoma seems rare. All studied cases concerned adults or adolescents; this paper reports the first infant presenting urachal mucinous cystadenoma. Case report: A seven-month-old boy affected by urachal mucinous cystadenoma, presented as only sign persistent purulent umbilical discharge. Ultrasonography showed nodular structure with liquid content evoking urachal cyst. Radical surgical excision was performed. Histopathology proved diagnosis of urachal mucinous cystadenoma. No complications were observed. Follow-up consultation eight days postoperative was reassuring, evaluating infection and recurrence absence, and scar healing. Discussion: Preservation of urachus lumen may lead to urachal diseases: patent, diverticulum, sinus and cyst. Mucinous cystadenoma is rarely found in urachus. Solely umbilical purulent discharge was observed, in contrast to all reported cases. Same type of investigation, ultrasonography, was conducted to evoke diagnosis. Since urachal mucinous cystadenoma may transform into adenocarcinoma, prophylactic excision is recommended, and prognosis depends on its radicalness. No long-term outcome for infants is available in literature. We propose annual follow-up by ultrasonography. Conclusion: Urachal mucinous cystadenoma in infants is uncommon. Umbilical discharge must indicate ultrasonography. Surgical excision is recommended in case of suspicion. Long term outcomes are yet to be evaluated.